Analysis of VAK Learning Styles of VIII Grade Students in Science - Nailatus Sholihah, Nailatus Sholihah; Erna Wijayanti (Universitas Tidar, 2023)
Science learning is a process that is intentionally designed to facilitate the process of learning science. Based on initial observations made by researchers, it is known that MTs Nahjatus Sholihin students have not understood their respective learning styles, so students have been unable to maximize them in the science learning process. This study aims to analyze the VAK (Visual, Auditorial, Kinesthetic) learning styles of VIII-grade students in science subjects at MTs Nahjatus Sholihin, Rembang Regency. This research is quantitative descriptive research. The subjects of this study were all VIII-grade students at MTs Nahjatus Sholihin, with a total of 86 students. This study used the total sampling technique. Data collection methods were carried out through observation, questionnaires, and documentation. Based on the results of observations, it is known that from each class VIII that was analyzed for learning styles, the highest percentage of students had a kinesthetic learning style, with a percentage of 45% in class VIIIA, 40% in class VIIIB, and 41% in class VIIIC, while the lowest percentage of students had a visual learning style with a percentage of 22% in class VIIIA, 29% in class VIIIB, and 28% in class VIIIC.